Analysis Of Student Characteristics Of Professional AUD Educators - Gella, Adefia Marsa; Ulandari , Zuzanti; Sari , Novita; Febriana , Dhera Calista; Pebriani , Ela (CV. Generasi Insan Rafflesia, 2025)
This study aimed to examine in depth the professional characteristics of educators in Early Childhood Education (PAUD) services in Indonesia. Through a literature review approach and analysis of educational policy documents, the study discussed four main aspects of educator competence, namely pedagogical, professional, social, and personal competence. In addition, it analyzed the attitudes, behaviors, and work ethics that reflected the professionalism of PAUD educators in their daily practice. The findings showed that professional PAUD educators were not only characterized by mastery of knowledge and teaching skills but also by reflective, collaborative, and adaptive abilities toward technological developments, as well as a commitment to inclusive learning. The main challenges faced included the lack of continuous training and institutional support. Therefore, capacity-building strategies were needed through sustainable professional development programs, mentoring, and policies that supported the well-being of PAUD educators so that their professionalism could develop optimally and sustainably.